2005
DOI: 10.1007/s10680-004-6756-9
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Impact of Education on Entry into Motherhood

Abstract: Lappega˚rd T. and Rønsen M., 2005, The multifaceted impact of education on entry into motherhood, European Journal of Population 21: 31-49.Abstract. This article studies the composite effect of education on young women's entry into motherhood, using longitudinal data from Norway from 1971 to 2001. In line with previous research, we find that school enrolment delays motherhood, but having finished education there is a catching-up effect, as women who have completed at higher levels have their first child sooner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
168
1
11

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(203 citation statements)
references
References 25 publications
9
168
1
11
Order By: Relevance
“…This implies that higher educated women have more to lose by staying at home to provide childcare -a situation aggravated by the persistence of traditional gender role division, particularly in East Asia (see Box 2). These higher opportunity costs of childbearing may contribute both to the delay and decline of fertility (Kravdal 2004;Lappegård and Rønsen 2005;Gustafsson 2005). But education effects are likely not confined to financial issues.…”
Section: Educationmentioning
confidence: 99%
“…This implies that higher educated women have more to lose by staying at home to provide childcare -a situation aggravated by the persistence of traditional gender role division, particularly in East Asia (see Box 2). These higher opportunity costs of childbearing may contribute both to the delay and decline of fertility (Kravdal 2004;Lappegård and Rønsen 2005;Gustafsson 2005). But education effects are likely not confined to financial issues.…”
Section: Educationmentioning
confidence: 99%
“…To capture full-time education rather than participation in shorter courses, educational enrolment is defined as enrolment for at least 4 months of the previous year. Educational attainment also affects earnings as well as fertility decisions (see e.g., Kravdal and Rindfuss 2008;Lappegård and Rønsen 2005), and is therefore included in the model. Unemployment may affect fertility through reducing income, but also through creating uncertainty about future economic prospects (see e.g., Kreyenfeld 2010).…”
Section: Variablesmentioning
confidence: 99%
“…Blossfeld and Huinink (1991) have argued that it is these transition norms in combination with the increased period spent in education which result in a delay in motherhood. A number of studies have shown that after graduating, highly educated women have their first child more quickly than less educated women because they feel their reproductive period has been greatly curtailed by the years they spent in education (Blossfeld 1995;Gustafsson, Kenjoh, and Wetzels 2002;Gustafsson 2005;Hank 2002;Kravdal 1994;Lappegård and Rønsen 2005;Liefbroer and Corijn 1999;Skirbekk, Kohler, and Prskawetz 2004). …”
Section: The Complex Interplay Between Education Family and Workmentioning
confidence: 99%
“…Education seems to play a crucial role, as a wide range of studies have shown that an individual's educational level can affect (the timing of) his or her family formation decisions and labour outcomes Krause 2002, 2003;Budig and Hodges 2010;Dex et al 1998;Gustafsson 2003;Liefbroer and Corijn 1999;Rindfuss, Morgan, and Offutt 1996). The amount of time young people spend in education or a field of education has been studied to a lesser extent, but the existing work has indicated that this factor is also non-negligible (Blossfeld and Huinink 1991;Hank 2002;Hoem 1986;Kalmijn 1996;Kreyenfeld 2000;Lappegård 2002;Lappegård and Rønsen 2005;Van Bavel 2010).…”
Section: Introductionmentioning
confidence: 99%